Evaluation of the growth and yield of the tomato crop (Solanum lycopersicum) variety Shanty and hybrid DRD 8551, under the conditions of Cubiro State Lara Venezuela (Agroindustria, Sociedad y Ambiente, 2025)
The tomato is a bush-type plant that is grown as an annual plant. There are two types of plants: determinate, whose growth is limited, and indeterminate with unlimited growth. The objective of this work was to compare the agronomic adaptation of a variety and a specific tomato hybrid, in order to select the one with the best quality and performance characteristics. The trial was carried out on the La Neblina farm located 09° 46'38.54" N and 69° 35'24.76" W, at 1710 m.a.s.l.  The design used was in completely randomized blocks with 5 repetitions that allowed the evaluation of the two tomato materials, the DRD8551 hybrid and the Shanty variety. The variables measured were: plant height. The number of fruits per inflorescence/plant, weight and yield. In the case of plant height, the Shanty variety reached 201.18 cm, while Numeral reached 173.46 cm. The number of flowers per plant was greater in the Numeral hybrid (DRD 8551), in the same way it produced a greater number and weight. in the fruits compared to the Shanty variety, the numeral hybrid produced 35,619 kg/ha, while the Shanty variety yielded 13563 kg/ha By considering that both the number and weight of fruits per plant are the components that directly intervene in the yield, it can be explained that the Numeral hybrid produced greater numbers of fruits and with greater weight per plant, which is why its yield was higher. unlike the Shanty variety
Keywords: Solanum lycopersicum, yield, fruit weight.